2001
DOI: 10.1097/00004647-200105000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Glucose Transport in Human Brain Gray and White Matter

Abstract: Summary:Localized 1 H nuclear magnetic resonance spectroscopy has been applied to determine human brain gray matter and white matter glucose transport kinetics by measuring the steady-state glucose concentration under normoglycemia and two levels of hyperglycemia. Nuclear magnetic resonance spectroscopic measurements were simultaneously performed on three 12-mL volumes, containing predominantly gray or white matter. The exact volume compositions were determined from quantitative T 1 relaxation magnetic resonan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
93
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(110 citation statements)
references
References 36 publications
17
93
0
Order By: Relevance
“…Such a model has been proposed, 21,128 and it was shown that one implication of the reversible model of brain glucose transport is that the relationship between brain and plasma glucose is linear. 21 Many measurements of brain glucose content as a function of plasma glucose have in the meantime corroborated the observation that brain glucose concentrations are a linear function of plasma glucose, 24,115,129,130 and such a case is illustrated for two different anesthetic regimes, -chloralose and pentobarbital in Fig. 11(A).…”
Section: Glucose Transportmentioning
confidence: 83%
See 1 more Smart Citation
“…Such a model has been proposed, 21,128 and it was shown that one implication of the reversible model of brain glucose transport is that the relationship between brain and plasma glucose is linear. 21 Many measurements of brain glucose content as a function of plasma glucose have in the meantime corroborated the observation that brain glucose concentrations are a linear function of plasma glucose, 24,115,129,130 and such a case is illustrated for two different anesthetic regimes, -chloralose and pentobarbital in Fig. 11(A).…”
Section: Glucose Transportmentioning
confidence: 83%
“…21,22,115,129,130 A recent study extended the brain glucose concentrations measurements to hypoglycemia using 13 C NMR spectroscopy. 24 The concentrations measured by 13 C NMR were found to be in excellent agreement with those predicted by the reversible MichaelisMenten model as well as those measured by 1 H NMR spectroscopy [ Fig.…”
Section: Glucose Transportmentioning
confidence: 99%
“…However, these transporters catalyze bi-directional fluxes, and the presence of intracellular and/or extracellular glucose alters the kinetics of transport both in and out of the cell. This bidirectional transport must be actively considered when modeling the flow of glucose from blood to the individual types of neural cells, primarily neurons and glial cells (see below Blomqvist et al, 1991;Carruthers, 1990;Choi et al, 2001;Cloherty et al, 1996;de Graaf et al, 2001; Gjedde, 1980; Gruetter et al, 1998; Hebert and Carruthers, 1991;Qutub and Hunt, 2005).…”
Section: Kinetics Of Glucose Transportmentioning
confidence: 99%
“…However, these transporters catalyze bi-directional fluxes, and the presence of intracellular and/or extracellular glucose alters the kinetics of transport both in and out of the cell. This bidirectional transport must be actively considered when modeling the flow of glucose from blood to the individual types of neural cells, primarily neurons and glial cells (see below Blomqvist et al, 1991;Carruthers, 1990;Choi et al, 2001;Cloherty et al, 1996;de Graaf et al, 2001; Gjedde, 1980; Gruetter et al, 1998; Hebert and Carruthers, 1991;Qutub and Hunt, 2005).The capacity for glucose transport depends on the concentration of the transporter proteins as well as their intrinsic catalytic turnover activity or number of transport cycles catalyzed per transporter per sec (k cat ) within the respective cellular compartments. It is relatively easy to determine the total concentration of GLUTs in brain microvessels, as these vessels can be readily isolated from whole brain (Vannucci, 1994).…”
mentioning
confidence: 99%
“…However, in order to take into account the different concentrations of metabolites in GM and WM, the two compartments were assigned different concentrations of glutamate (Glu), glutamine (Gln), aspartate (Asp), and lactate (Lac). The ratio [Glu] WM /[Glu] GM was set to ϳ0.5 according to human data (33,34) Metabolic fluxes and glutamate ADC in GM and WM were adjusted by minimizing the difference between the four measured and simulated time-courses for glutamate Ci enrichment (with i ϭ 3 and 4). At each step of the minimization procedure, Ci enrichment time-courses in GM and WM were generated for the tested values of V TCA GM , V X GM , V TCA WM , and V X WM by solving differential equations describing 13 C incorporation.…”
Section: Gm-wm Metabolic Modeling Including Diffusion Weightingmentioning
confidence: 99%